A survey of undergraduates’ use of library resources in university of Ibadan: does discipline affect library use? (2012)
Use of library resources and factors that hindered use by undergraduates in Social Science and Science disciplines in University of Ibadan was investigated. Random sampling was used to select two and three departments from social science and science respectively and a sample size of 218. Questionnaire was used for data collection. Results showed that print resources were more available for use than electronic resources in both disciplines. Majority of the social science students used the resources for examination and assignment (52.6%), while those in science used them more for examination purposes (57.8%). Books were accessible to students in both disciplines but journals, research projects and dictionaries were more accessible to social science students than science students. Social science students used books, journals, research projects and dictionaries more frequently than science students. The undergraduates in both disciplines expressed that unavailability of library resources, erratic electricity power supply, and improper preservation of library resources, obsolete materials and inadequate ICT facilities hindered their use of library resources. The use of library resources was determined by their accessibility and discipline of the undergraduates.